Slovo k izbirateliu . Slovo k izbirateliu . Address to the Electorate . Слово к избирателю - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Vladimir Zhirinovskii, leader of Liberal Democratic Working Party of Russia, discusses the state and its borders; promotional video by "Russia's Choice" electoral bloc. Featured in the program: Zhirinovskii, Vladimir Vol'fovich (Politician); Pamfilova, Ella Aleksandrovna (Minister of Social Welfare of the Russian Population); Dolina, Larisa Aleksandrovna (Singer) Владимир Жириновский, лидер Либерально-Демократической Партии России, рассуждает на тему государства и его границ; рекламный ролик избирательного блока "Выбор России.". В программе участвуют: Жириновский, Владимир Вольфович (Политик); Памфилова, Элла Александровна (Министр социальной защиты населения России); Долина, Лариса Александровна (Певица)